Lack of a support system for people infected and affected by HIV and AIDS in the workplace : can emotional and psychosocial support assist them to cope better with their problems? - Twalo, Lindelwa Princess (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2006.